2012
DOI: 10.1155/2012/789653
|View full text |Cite
|
Sign up to set email alerts
|

Androgens and Adipose Tissue in Males: A Complex and Reciprocal Interplay

Abstract: Clinical evidence shows that in males obesity is frequently associated with hypogonadism and vice versa; also, low testosterone levels have been considered a “hallmark” of metabolic syndrome in men. These observations indicate that there is a strict connection between anatomically and functionally distinct cell types such as white adipocytes and Leydig cells, that synthesize testosterone. Adipose tissue is able to control several functions of the testis through its products secreted in the bloodstream. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 89 publications
4
73
0
8
Order By: Relevance
“…However, the HFS rats also showed a decrease in plasma testosterone levels, a finding consistent with previous clinical reports which demonstrated that obesity in men is associated with low testosterone levels (Barrett-Connor 1992, Andersson et al 1994, Grossmann 2013, Mogri et al 2013. The reduction of testosterone levels in the HFS rats could be a factor in the decrease in the hypothalamo-pituitary-gonadal axis due to inflammation following obesity as decribed in previous studies (Cohen 1999, Gregor & Hotamisligil 2011, Mammi et al 2012, Jayaraman et al 2014b. Although it has been shown that obesity could increase the estrogen levels in female rats (Pratchayasakul et al 2011), our previous study demonstrated that 12 weeks of high-fat diet feeding did not affect the circulating estrogen levels in male rats (Pratchayasakul et al 2011).…”
Section: Discussionsupporting
confidence: 88%
“…However, the HFS rats also showed a decrease in plasma testosterone levels, a finding consistent with previous clinical reports which demonstrated that obesity in men is associated with low testosterone levels (Barrett-Connor 1992, Andersson et al 1994, Grossmann 2013, Mogri et al 2013. The reduction of testosterone levels in the HFS rats could be a factor in the decrease in the hypothalamo-pituitary-gonadal axis due to inflammation following obesity as decribed in previous studies (Cohen 1999, Gregor & Hotamisligil 2011, Mammi et al 2012, Jayaraman et al 2014b. Although it has been shown that obesity could increase the estrogen levels in female rats (Pratchayasakul et al 2011), our previous study demonstrated that 12 weeks of high-fat diet feeding did not affect the circulating estrogen levels in male rats (Pratchayasakul et al 2011).…”
Section: Discussionsupporting
confidence: 88%
“…[6] However, it is unclear whether plasma leptin level affects the production of testosterone or dihydrotestosterone in the local environment of hair follicles, which has more implication in the development of AGA than systemic androgens. [7] The interaction between dermal adipose tissue and hair follicles is receiving more attention currently.…”
Section: It Is Known That Excess Of Plasma Leptin Has a Negative Impamentioning
confidence: 99%
“…1 The main endocrine derangements of KS include decreased secretion of androgens, increased plasma gonadotrophins, small testes and azoospermia. 1 Patients with KS have a higher prevalence of metabolic syndrome (MetS) and cardiovascular abnormalities, accounting for the increased risk of dying from heart disease.…”
Section: Dear Sirmentioning
confidence: 99%
“…1 The main endocrine derangements of KS include decreased secretion of androgens, increased plasma gonadotrophins, small testes and azoospermia. 1 Patients with KS have a higher prevalence of metabolic syndrome (MetS) and cardiovascular abnormalities, accounting for the increased risk of dying from heart disease. [1][2][3] MetS is closely associated with a low-grade chronic inflammatory status characterized by abnormal cytokine production, which activates a network of inflammatory signalling pathways.…”
Section: Dear Sirmentioning
confidence: 99%
See 1 more Smart Citation